Factors Affecting Interests of Adolescent Visit in Poly PKPR (Health Care Service) Public Health Gondang Legi Malang District - Evi Kurniawati; Nurwijayanti Nurwijayanti; Agusta Dian Ellina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
A person's interest in services is related to the ability of these service providers to provide care. Interest in adolescents to take advantage of adolescent health care services is influenced by several factors, including perceptions, peers and the role of health workers in the service at puskesmas. The purpose of this study was to analyze the factors that influence the interest of teenage return visits at the PKPR (Youth Caring Health Services) Gondang Legi Health Center in Malang Regency. The design of this study was an observational quantitative study with a cross sectional approach with the focus of the research directed to be analyzing perceptions, the role of peers and the role of health workers on the interest of teenage return visits at the PKPR (Youth Care Health Services) Gondang Legi Public Health Center Malang Regency with a population of 167 respondents and a sample of 113 respondents taken by accidental sampling technique. The findings found that the majority of respondents had less categories of perception as many as 57 respondents (50.4%). In addition, the majority of respondents had the role of less peer categories of 45 respondents (51.3%). In addition, most respondents had the role of health workers in the good category of 59 respondents (52.2%). While the majority of respondents had a high interest category of 62 respondents (54.9%). The results of the study using the Logistic Regression Test showed that a p-value of 0,000 <0.05 then H1 was accepted so it was concluded that there was simultaneously the influence of perception, the role of peers and the role of health workers on the interest of teenage returnees in the PKPR (Youth Care Health Services) ) Gondang Legi Health Center in Malang Regency. The perspective of the patient regarding the available health services raises their perceptions. All friends will make an impact on individuals. And the provision of special services to adolescents through special treatment tailored to the desires, tastes and needs of adolescents has not been implemented